Exploring Metacognitive Writing Strategies in the Writing Process using Think aloud Protocol: A Study across Gender - Aripin, Norhartini; Rahmat, Noor Hanim (American Journal of Social Sciences and Humanities, 2019)
ESL Writing is a learning skill that is considered as a challenge for ESL writers. To acquire this skill, ESL writers should actively involve in the writing process. This process requires them to apply some strategies. These writing strategies function as a writing controller that guides the writers to produce a good text. Metacognitive writing strategies is one of the writing strategies that comprises of three main components namely, planning, monitoring and evaluating. Hence, this study aims to explore metacognitive writing strategies used by students who are enrolled in an English course. The course is known as Integrated Language Skill (Writing). Three students from one public university in Johor, Malaysia are grouped according to their gender. This qualitative study used Think-aloud protocol (TAP) as the main method in collecting data. Findings revealed that both male and female ESL writers used a variety of metacognitive writing strategies in their writing process. The female writer used more strategies compared to the male writer. Results of this study provide useful implication towards teaching and learning of ESL academic writing.